Synthesis of oleic acid capped copper nano-particles via reduction of copper salt by SFS - Khanna, P. K.; Kale, Trupti S.; Shaikh, Mushtaq; Rao, N. Koteswar; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2008)
Synthesis of oleic acid capped copper nano-particles has been carried out by use of sodium formaldehyde sulfoxylate (SFS) in aqueous medium. Nano-copper can be effectively coated with polyvinyl alcohol (PVA). Phase-pure nano-Cu can be obtained when water/acetone was used as aqueous medium. It is observed that the surface plasmon resonance (SPR) phenomena can be controlled during synthesis by the use of suitable reagent system, e.g. absorption band in presence of PVA can be blue shifted. As-prepared copper nano-particles were characterized by X-ray diffraction measurements (XRD), Scanning electron microscopy (SEM), energy dispersive analysis of X-rays (EDAX), thermo gravimetric analysis (TGA) and Fourier transform infra-red spectroscopy (FTIR). XRD analysis revealed broad pattern for fcc crystal structure of copper metal. The particle size by use of Scherrer's equation was calculated to be about 20 nm. TGA revealed similar to 10% weight loss due to the presence of surfactant. FTIR spectroscopy confirmed the presence of oleic acid around the particles. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; metals; Nanostructure